Exploration of relationship patterns and family functioning in polygamous families: a pilot study - Muhammad Ajib Abd Razak; Intan Hashimah Mohd Hashim; Syazwani Drani (Penerbit Universiti Kebangsaan Malaysia, 2020)
The mostly Muslim nation of Malaysia has been unwavering in its perceptions about the practice of polygamy. These perceptions remain negative, reflecting the lamentable experiences of various families involved in polygamy. The lack of exploration of positive elements in polygamous families causes conflicts and household problems to be difficult to resolve. Thefore, this study was conducted to ascertain the suitability of the interview questions and test the study objectives. This pilot study used a fully qualitative method and one family was interviewed. The results revealed that, harmonious environment, sharing open communication, responsiveness, sharing fun things, focusing on themselves, complementing each other, provision of God, not rigid, good communication, accustomized and integrating and understanding their role are the several major themes in the pattern of the relevant relationships. Further, all family members tend to perform very well, have mature minds and enjoy broader and better social networks to describe family functioning in the general context. This pilot study potrayed a functioning family involved in polygamy but also suggested some improvements to the content of questions, the criteria of potential respondents, and the time allocated, as well as an enhancement of communication between researchers and respondents.